2014
DOI: 10.5812/ijhrba.21765
|View full text |Cite
|
Sign up to set email alerts
|

Compulsory Maintenance Treatment Program Amongst Iranian Injection Drug Users and Its Side Effects

Abstract: Background:Psychoactive substance use can cause a broad variety of mental health disorders and social health problems for the drug users, their family and society.Objectives:The Ministry of Health, Treatment, and Medical Education of Iran has recently proclaimed an estimated number of 2 million drug abusers and 200,000 injecting drug users (IDUs).Patients and Methods:For data collection, the directory of mental, social health, and Addiction designed a questionnaire in cooperation with Drug Control Headquarters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…Reports and evaluations of the two recent decades in Iran have indicated that primary health care had been influential and succeeded in delivering health services particularly once integrating with mental health affairs (25)(26)(27). Studies need to consider potential and practical strategies if they intend to be productive; staff training, educating the community, concerning preventive measures and reducing harm for substance drug users are among of necessary factors (23)(24)(25)(26)(27)(28). Results of the present study are consistent with other studies (19), and support the notion that it will be significantly effective if professionals integrate preventive and intervention programs in PHC and health services.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Reports and evaluations of the two recent decades in Iran have indicated that primary health care had been influential and succeeded in delivering health services particularly once integrating with mental health affairs (25)(26)(27). Studies need to consider potential and practical strategies if they intend to be productive; staff training, educating the community, concerning preventive measures and reducing harm for substance drug users are among of necessary factors (23)(24)(25)(26)(27)(28). Results of the present study are consistent with other studies (19), and support the notion that it will be significantly effective if professionals integrate preventive and intervention programs in PHC and health services.…”
Section: Discussionsupporting
confidence: 86%
“…The program encountered some challenges in Iran; and the PHC requires a more holistic, community-based and comprehensive approach in order to obtain clear and firm outcomes. One of the challenges related to policymaking and law issues is removal, such difficulties that may result in more precise preventive outputs (24)(25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…These results have shown that this program was approximately successful in decreasing drug users' stress indicators [8]. …”
Section: Resultsmentioning
confidence: 99%
“…Upon entrance to the rehabilitation center, the aim of the interview was explained to subjects and, after obtaining consent to participation, the questionnaire was completed for each individual via a face-to-face interviews, which were in-depth, semistructured interviews conducted by 3 social workers and 1 clinical psychologist [7, 8]. Qualitative data that were collected through semistructured interviews including the subjects' self-report reasons regarding substance use were extracted via the following questions: “How did you get involved in substance addiction?” and “What was your main reason of substance use?”.…”
Section: Methodsmentioning
confidence: 99%
“…Few countries offer agonist opioid treatment in detention centers, with the exception of Iran, where compulsory mandatory treatment centers offer methadone therapy (Eskandarieh, Jafari et al 2015). Rigorous evidence indicates that voluntary, community-based treatment programmes are more effective in treating addictions than compulsory treatment modalities.…”
Section: Discussionmentioning
confidence: 99%